Pengaruh Pemanfaatan E-Learning Terhadap Prestasi Belajar Mahasiswa (Studi Kasus STMIK Sinar Nusantara Surakarta) - Sri Tomo, Bebas Widada (STMIK Sinar Nusantara, 2014)
College are required to implement the learning process by making use of information and communication technologies, facing many obstacles that are not simple. The main problem that is often faced by the college is limited infrastructure, human resources and learning resources. While the lecturers is limited knowledge about the management of e-learning, and motivation of lecturers in the use of e-learning as a learning medium. This study aims to examine the use of e-learning by faculty as instructional media and its influence on motivation, performance and student learning outcomes in higher education. This research method with a questionnaire distributed to 100 students in e-learning users STMIK Sinar Nusantara. Questionnaire was tested with validity and reliability. Hypothesis is tested using linear regression techniques. The results showed the use of e-learning affect the motivation of learning, e-learning has a positive effect on student performance, motivation to learn a positive effect on learning outcomes, Readiness positive effect on learning outcomes, and e-learning has a positive effect on student learning outcomes.Keyword : e-learning, motivation of learning, readiness, student performance, student learning outcomes